The effect applying different rate of nitrogen fertilizer on rice / Natasha Husna Zakariah (Faculty of Plantation and Agrotechnology, 2016)
Rice is a food which consume daily by almost 7 billion people in the world. The rice consumption increase proportionally with population however, the yield declining. A decline production of rice caused by many factors and one of the factor is nutrient management especially nitrogen fertilizer. Nitrogen is a basic nutrient needed by rice and helps in maintain the rice yield (Guindo et al, 1994; Pang et al, 2002; Liu et al, 2007; Yang et al, 2011). The quality and yield of rice can be increase if nitrogen was manage wisely (Chaturvedi, 2015). The rate on nitrogen fertilizer give significant effect to growth, yield, and others. This paper highlighted the effect of applying difference rate of nitrogen fertilizer growth and yield of rice.